Model for the evaluation of drug-dispensing services in primary health care - Vanessa de Bona Sartor; Sergio Fernando Torres de Freitas (Universidade de São Paulo, 2014)
OBJECTIVE To develop a model for evaluating the efficacy of drug-dispensing service in primary health care. METHODS An efficacy criterion was adopted to determine the level of achievement of the service objectives. The evaluation model was developed on the basis of a literature search and discussions with experts. The applicability test of the model was conducted in 15 primary health care units in the city of Florianópolis, state of Santa Catarina, in 2010, and data were recorded in structured and pretested questionnaires. RESULTS The model developed was evaluated using five dimensions of analysis for analysis. The model was suitable for evaluating service efficacy and helped to identify the critical points of each service dimension. CONCLUSIONS Adaptations to the data collection technique may be required to adjust for the reality and needs of each situation. The evaluation of the drug-dispensing service should promote adequate access to medications supplied through the public health system.